(3eSfO GdHRGQs - (3CHh HcQ CMeO Hf YeQh Hf YHO GdNGdb GdHRGQ,J (B292 (3g` s
(3ChdgG (B:s
(3jHJOF HHbjI eSfO CHj HcQ GdUOjb QVi Gddg Yfg Hbhdg (B: (3MOKfG eMeO Hf GdeKfi , bGd (B: (3fGQhM GHf YHGOI , bGd (B: (3fGehSi Hf YHjO , bGd (B: (3MOKfi ehdi Hf SHGY, bGd SeYJ YHO Gddg GHf YeQ s
(3BNQgG (B:s
(3hjfJgi HdBNQ eSfO YHO Gddg Hf eSYhO QVi Gddg Yfg s
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B189s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B4 - (3U (B99 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd s
Keywords: (3GdMOjK h GdeUWdMs